Hematological and Biochemical Assessment of Children Infected with Measles Virus: 2022 Outbreak in Pakistan: Measles’s Hematological and Biochemical Assessment - Asiya Nawaz; Asim Saeed; Sidra Rahman; Nighat Haider (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Measles is a contagious disease caused by an RNA virus. Resurgence of measles after Covid-19 and its severity among children has led to many speculations about the Measles vaccination coverage and its efficacy. In this study, the clinical data of children <9 years (n=19) admitted at the Pakistan Institute of Medical Sciences (PIMS) in the measles ward was analyzed. The blood samples were processed for hematology and routine biochemistry tests. The results obtained were statistically analyzed on SPSS-21 software by using One-Way ANOVA for Complete Parameters (CP), Kruskal Wallis, and Mann-Whitney test for Differential leucocyte count (DLC) and Biochemical parameters. A p<0.05 was considered significant. The results suggest no significant difference in Complete blood parameters (CP) among non-vaccinated, partially vaccinated and fully vaccinated patients. Among DLC Basophils level was significantly different (p=0.024), being lower in partially vaccinated than non-vaccinated patients. Biochemical parameters showed that serum urea level was significantly different (p=0.013), showing a decline in fully vaccinated patients as compared to non-vaccinated patients. Moreover, a significantly higher level of Alkaline phosphatase as compared to the normal range was observed in fully vaccinated patients. However, lower levels of MCH, MCV, MCHC, RBC, Hb, eosinophils, and a higher level of RDW-CV were observed overall as compared to the normal range (healthy individuals). The results suggest improvements are needed in vaccination strategies for effectively controlling the disease. Anemic conditions in overall measles patients indicate poor health conditions. This study contains a limited sample size, further research on measles virus (MeV) mutations, and vaccine optimization could be helpful for the complete eradication of measles from Pakistan.